Impact of Multiscale Heterogeneous Sediments and Boundary Conditions on Dispersivity Spatial Variations - Ziqi Ma; Linlin Qi; Zhenxue Dai; Zhijie Yang; Yue Ma; Dayong Wang; Kenneth C. Carroll; Mohamad Reza Soltanian (Water Resources Research)
Abstract This study investigates the factors influencing the scale dependence of dispersivity and the dispersivity upscaling theory in heterogeneous sediments. A series of tracer experiments are first conducted to reveal the evolution of dispersivity across scales. These experiments contain various sedimentary structures, including several nearly‐homogeneous column tests, a heterogeneous column test, a horizontally stratified tank experiment, a randomly filled tank experiment, and a three‐dimensional tank experiment utilizing an analogous simulation to a field‐scale site. The impact of impervious boundaries, sedimentary architectures, and heterogeneity on the dispersivity scaling is assessed by controlling transport distance, setup dimension, facies volume proportions, and facies distribution. Finally, the Lagrangian‐based models, applicable for bounded and unbounded sediments, are employed to examine the relationship between various heterogeneous structures and dispersivity variations. The results indicate that the transport uncertainty introduced by dispersivity scaling is relatively weak in nearly‐homogeneous or stratified media but prominent in complex heterogeneous media. Hydraulic conductivity variance and space correlation structure in sediments contribute greatly to the value and increased rate of dispersivity. The predictive capabilities of transport models can be significantly improved by incorporating detailed facies indicator data and accounting for sediment heterogeneity. Although the impervious boundary enhances longitudinal dispersion by restricting transverse dispersion, the promoting effect decreases with the boundary spacing. The Lagrangian‐based models with detailed facies indicator data effectively capture the dispersivity variation trend with travel distance. The complementary use of the bounded and unbounded models can help better identify the scale‐dependent dispersivities, ultimately leading to more effective contaminant mitigation strategies.